Melena - a rare clinical presentation in a patient with ruptured tubal ectopic pregnancy - Malkeet Kaur; Kavita Babbar; Devendra Singh; Aman Sharma (Barpeta Obstetrics and Gynaecological Society, 2021)
Ectopic pregnancy is a medical emergency which requires immediate intervention and may lead to death if left untreated. Patients usually present with abdominal pain, vaginal bleeding but may also present with signs of shock due to blood loss. We report a case of 32 years old patient who presented with melena as her chief complaint, did not mention history of amenorrhea but was later diagnosed as a case of ruptured ectopic tubal pregnancy.